Effect of Propolis Trigona Sp on Expression of TNF-α in Superficial Dermal Burns through In Vivo Test - Siwabessy, Melfrits R.; Manginstar, Christian; Merung, Marselus A.; Langi, Fredrik G. L. (e-CliniC, 2024)
Abstract: Burn is caused by exposure to high-temperature substances such as hot, solid liquids or gases such as smoke, steam, engines, stoves, radiators and objects that emit heat energy. In severe burns, there is an excessive neutrophil inflammatory response that triggers SIRS, where there is an excessive increase in pro-inflammatory mediators such as TNFα and IL-6. Propolis contains a number of compounds, such as flavonoids, CAPE, phenol compounds, arginine, ferulic acid and albumin which play a good role in healing burns. This study aimed to find out the effect of propolis on TNF-α expression through in-vivo testing in cases of superficial dermal burns. This was an experimental and laboratory study to assess the bioactive compounds contained in Trigona Sp propolis. Descriptive analysis was performed on the bioactive composition of Trigona Sp propolis and experimental effectiveness of propolis on TNF-α expression in superficial dermal burns. The study was conducted at the laboratory of experimental animals "Alike Quality System", Manado. The results showed that the group treated with propolis had smaller burn areas compared to the groups treated with 1% silver sulfadiazine or with 0.9% NaCl. Granulation had been formed throughout all wounds, however, macroscopically, burns with propolis treatment showed reddish wound appearance while treated wounds with 1% silver sulfadiazine and 0.9% NaCl were darker in color and had thicker crust formation. The one-way ANOVA test showed no significant difference between propolis and 1% silver sulfadiazine on TNF-α expression in dermal superficial burns (p=0.666) meanwhile the effect of propolis compared with NaCl 0.9% on TNF-α expression in dermal superficial burns, showed significant differences (p=0.006 and p=0.040). In conclusion, administration of propolis can reduce the expression of TNF-α in superficial dermal burn. Keywords: propolis; Trigona sp; burns; in vivo study